2019
DOI: 10.21203/rs.2.9381/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Estimating the annual risk of infection with Mycobacterium tuberculosis among adolescents in Western Kenya in preparation for TB vaccine trials

Abstract: Background: Adolescents are a prime target group for tuberculosis (TB) vaccine trials that include prevention of infection (POI). The BCG vaccine is given at birth and does not prevent TB infection. TB infection, a critical endpoint for POI vaccine trials would need to be documented to estimate sample sizes in target populations. Methods: Adolescents aged 12-18 years of age were enrolled in an area under continuous demographic surveillance. A tuberculin skin test (TST) survey was conducted as part of a study o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…The prevalence of positive QFT at enrolment for the entire cohort was 32% with a cumulative prevalence of 46% after three years of follow-up at a median age of 15 years. This is similar to the prevalence reported in Western Kenya where at 14.4 years the prevalence of TB infection (using Tuberculin skin testing) was also 32%; however, only 0.5% adolescents were living with HIV in that study and 41% had unknown HIV status [14]. The prevalence in our study is similar to the 53% prevalence reported in Cape Town in 2011 in adolescents between 14 and 17 years [13].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The prevalence of positive QFT at enrolment for the entire cohort was 32% with a cumulative prevalence of 46% after three years of follow-up at a median age of 15 years. This is similar to the prevalence reported in Western Kenya where at 14.4 years the prevalence of TB infection (using Tuberculin skin testing) was also 32%; however, only 0.5% adolescents were living with HIV in that study and 41% had unknown HIV status [14]. The prevalence in our study is similar to the 53% prevalence reported in Cape Town in 2011 in adolescents between 14 and 17 years [13].…”
Section: Discussionsupporting
confidence: 89%
“…Mtb infection can be measured using Interferon Gamma Release assays (IGRA), for example Quanti-FERON (QFT), a positive test denotes TB infection, however, further signs and symptoms and bacteriological evidence needs to be sought before the diagnosis of "TB disease" is made. Previous estimates of Mtb infection prevalence among adolescents in sub-Saharan Africa have indicated high annual risks among the general population but often lack data on HIV status [13,14]. In addition, a recent review that focused on bacteriologically confirmed pulmonary Tuberculosis (PTB) in adolescents and youth found no studies among those with HIV [15].…”
Section: Introductionmentioning
confidence: 99%